1997
DOI: 10.1097/00004647-199709000-00006
|View full text |Cite
|
Sign up to set email alerts
|

DNA Fragmentation Follows Delayed Neuronal Death in CA1 Neurons Exposed to Transient Global Ischemia in the Rat

Abstract: Summary: Apoptosis is an active, gene-directed process of cell death in which early fragmentation of nuclear DNA pre cedes morphological changes in the nucleus and, later, in the cytoplasm, In ischemia, biochemical studies have detected oli gonucleosomes of apoptosis whereas sequential morphological studies show changes consistent with necrosis rather than ap optosis, To resolve this apparent discrepancy, we subjected rats to 10 minutes of transient forebrain ischemia followed by I to 14 days of reperfusion, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
78
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(80 citation statements)
references
References 70 publications
1
78
0
Order By: Relevance
“…9,10 However, it is still unclear whether DNA fragmentation in hippocampal neurons after transient global ischemia is entirely due to the apoptotic pathway. 24 Also, the neuronal nature of the cells that exhibited DNA fragmentation is not clear at present. Further studies using double staining consisting of a neuronal marker (NeuN) and TUNEL are needed to address this issue.…”
Section: Discussionmentioning
confidence: 93%
“…9,10 However, it is still unclear whether DNA fragmentation in hippocampal neurons after transient global ischemia is entirely due to the apoptotic pathway. 24 Also, the neuronal nature of the cells that exhibited DNA fragmentation is not clear at present. Further studies using double staining consisting of a neuronal marker (NeuN) and TUNEL are needed to address this issue.…”
Section: Discussionmentioning
confidence: 93%
“…Recent studies, although still somewhat controversial, have identified some apoptotic features by biochemical and morphological evidence such as terminal deoxynucleotidyl transferase-mediated dUTP biotin nick end labeling (TUNEL) staining 14,31,32 and internucleosomal DNA fragmentation, as indicated by the DNA laddering pattern. 33 Several apoptosis-regulatory genes and enzymes are found to be induced in ischemic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies, although still somewhat controversial, have identified some apoptotic features by biochemical and morphological evidence such as TUNEL (MacManus et al, 1993;Sei et al, 1994;Petito et al, 1997) and internucleosomal DNA fragmentation as indicated by the DNA laddering pattern (Héron et al, 1993). Because TUNEL staining indicates DNA damage, and its specificity for apoptosis is questionable, we have used TUNEL staining only as an indication of DNA damage in cells.…”
Section: Reduction Of Neuronal Death and Dna Fragmentation In Vulneramentioning
confidence: 99%